Analisis Usia, Paritas, Status Gizi, dan Kadar Hemoglobin Pada Ibu Hamil - Sharief, Suchi Avnalurini; Suryanti, Suryanti (Jurusan Kebidanan Poltekkes Kemenkes Mamuju, 2025)
Anemia during pregnancy is a critical public health issue that poses significant risks to both maternal and fetal well-being, demanding immediate attention from all healthcare stakeholders. This condition can detrimentally impact the mother's health and hinder proper fetal growth and development. In Makassar City, the high prevalence of anemia is a pressing concern, with Rappokalling Health Center reporting 364 cases and Makkasau Health Center reporting 482 cases. This study was conducted to investigate the influence of maternal age, parity, and nutritional status on hemoglobin levels in pregnant women. This analytical survey utilized a cross-sectional design. The research population consisted of pregnant women making initial visits to two specific public health centers in Makassar City, with a total sample of 363 respondents. Data on maternal age, parity, nutritional status (measured by Upper Arm Circumference), and hemoglobin levels were collected through a documentation study using a checklist sheet. The data was then analyzed using cross-tabulation to determine the relationships between the variables. The study revealed a substantial prevalence of anemia, affecting 31.68% of the total sample. Specifically, anemia was found in 36.6% of pregnant women at Makkasau Health Center and 30.4% at Rappokalling Health Center. The findings indicated no statistically significant relationship between maternal age and hemoglobin levels, nor between parity and hemoglobin levels. However, a significant relationship was identified between nutritional status and hemoglobin levels. The data showed that 16.1% of pregnant women at Makkasau Health Center and 18.8% at Rappokalling Health Center had an abnormal dietary status, which was directly linked to lower hemoglobin levels. In conclusion, while maternal age and parity do not show a relationship with hemoglobin levels, nutritional status is a critical factor influencing anemia among pregnant women. These findings underscore the importance of nutritional intervention as a key strategy in mitigating the prevalence of anemia during pregnancy.